Superior sinterability of nano-crystalline gadolinium doped ceria powders synthesized by co-precipitation method - Prasad, D. Hari; Kim, H-R.; Park, J-S.; Son, J-W.; Kim, B-K.; Lee, H-W.; Lee, J-H. (ELSEVIER SCIENCE SA, 2010)
Reduced sintering temperature of doped ceria can greatly simplify the fabrication process of solid oxide fuel cells (SOFCs) by utilizing the co-firing of all cell components with a single step. In the present study, nano-crystalline gadolinium doped ceria (GDC) powders of high sinterability at lower sintering temperature has been synthesized by co-precipitation at room temperature. The successful synthesis of nano-crystalline GDC was confirmed by XRD, TEM and Raman spectroscopy analysis. Dilatometry studies showed that GDC prepared by this method can be fully densified (97% relative density) at a sintering temperature of 950 degrees C which is fairly lower than ever before. It has also been found that the sintered samples have a higher ionic conductivity of 1.64 x 10(-2) S cm(-1) at 600 degrees C which is suitable for the intermediate temperature SOFC application. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: OXIDE FUEL-CELLS; ELECTRICAL-PROPERTIES; HYDROTHERMAL SYNTHESIS; NANOCRYSTALLINE CERIA; ROOM-TEMPERATURE; SOLID-SOLUTIONS; ELECTROLYTES; MICROSTRUCTURE; 500-DEGREES-C; NANOPARTICLES